1996
DOI: 10.1111/j.1600-0447.1996.tb10647.x
|View full text |Cite
|
Sign up to set email alerts
|

Psvchotheraw and bulimia nervosa: eviluation and long‐term follow‐up of two conflict‐orientated treatment conditions

Abstract: Analytic in-patient therapy (n = 32) and systemic out-patient therapy (n = 39) were applied to patients with bulimia nervosa, and the effects were evaluated 14, 26 and 38 months after the start of the treatments. Our assumptions about the general efficacy of both conflict-orientated techniques were confirmed: both therapies satisfactorily reduced the symptomatic behaviour, as well as secondary factors related to bulimia nervosa, in the long term. However, we could not identify differential effects of the two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 25 publications
1
5
1
Order By: Relevance
“…All the patients had a high score for inhibition, confirming Jaeger's results (Jaeger et al, 1996) for the anorexics. In contrast, he found similar scores for bulimics and controls.…”
Section: Inhibitionsupporting
confidence: 85%
See 2 more Smart Citations
“…All the patients had a high score for inhibition, confirming Jaeger's results (Jaeger et al, 1996) for the anorexics. In contrast, he found similar scores for bulimics and controls.…”
Section: Inhibitionsupporting
confidence: 85%
“…In the context of the present study we are collecting FPI-R data at follow-up (2.5 years after entry into the 208 C. Massoubre et al study) and it will be interesting to determine whether personality traits persist or improve after treatment. Jaeger (Jaeger et al, 1996) showed with a small sample significant improvements after psychotherapy in four scales: life satisfaction, inhibition, extraversion and emotionality.…”
Section: Fpi-r Scores Changes Over Treatmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Some authors report the usefulness of interpersonal therapy [1, 9], others of psychodynamic psychotherapies [10, 11, 12]. …”
Section: Introductionmentioning
confidence: 99%
“…The literature has systematically indicated the propriety of applying psychotherapy in acute depressive states (Weissman et al, 1979) to maintain the benefits of the treatment (Weissman, 1994), and in combination with pharmacological treatment (Conti et al, 1986). Conclusions similar to those expressed in these articles are also present when other psychiatric pathologies are studied, such as anxiety disorder (Barlow & Lehman, 1996), drug addiction (Crits-Cristoph, 1996), and eating disorders (Jaeger et al, 1996). Texts which use meta-analytic statistical techniques arrive at conclusions that also clearly and consistently state that psychotherapies do have a therapeutic effect (Lipsey & Wilson, 1993;Shapiro & Shapiro, 1982;Crits-Cristoph, 1992).…”
Section: Current Situationmentioning
confidence: 59%